Pergeseran Budaya Pernikahan: Faktor-Faktor Penyebab Wali Nasab Melakukan Taukil Wali Kecamatan Kalitengah, Lamongan - Deni Arifianto; Imam Syahrul Mubarak; Thomas Badrut Tamam (Jaanur Elbarik Indonesia, 2026)
This study analyzes the cultural shift in marriage practices, specifically the high intensity of taukil wali (delegation of guardianship) by nasab guardians to third parties. While legally valid in Islamic jurisprudence, the growing tendency of guardians to avoid pronouncing the marriage vow reflects a shift in socio-religious behavior. This qualitative study, using a sociology of Islamic law approach, was conducted in Kecamatan Kalitengah, Kabupaten Lamongan. Data were gathered through in-depth interviews with KUA officials, marriage registrars, and guardians who delegated their authority. Findings reveal three primary drivers: psychological (anxiety and fear of error), educational (lack of understanding regarding the vows), and practical (the prevalence of